Sustainable Manufacturing Practices among Smes in Malaysia - Hami, Norsiah; Mat Yamin, Fadhilah; Mohd Shafie, Shafini; Muhamad, Mohd Razali; Ebrahim, Zuhriah (IJTech, 2018)
Small and medium enterprises (SMEs) play a significant role in the economic development of Malaysia. SMEs account for a large proportion of businesses, approximately 97.3% of establishments, in this country. While there is a plethora of studies on examining the commitments of large and multinational firms towards sustainability in business, little is known about the efforts of SMEs on translating their strategic orientation towards environmental and social sustainability into action. It is important to examine the extent of SMEs’ response to the imperatives of becoming sustainable businesses through the implementation of sustainable manufacturing practice (SMP) in business operations. The purpose of this paper is to determine the extent of the implementation of SMP among SMEs in Malaysia. Analysing a survey data from 127 SMEs, the results show that the extent of the implementation of SMP among SMEs is low to moderate. The result implies that though environmental initiatives are becoming important nowadays, there is still a lack of implementing SMP in operational and business activities among SMEs in Malaysia. While offering some insights on SMP particularly in the context of SMEs, this study provides a useful reference for salient stakeholders such as government and industrial practitioners in making decisions and further actions related to the strategies on nurturing, implementing and enforcing environmental protection and social well-being